Adverse childhood experiences and truancy in high school: an analysis of Florida adolescents - Boccio, Cashen (Deviant behavior, 2025)
Previous research links exposure to adverse childhood experiences (ACEs) with a host of negative outcomes, including negative school outcomes. For instance, some studies link exposure to ACEs with weak school attachment, school misbehavior, suspension, negative academic performance, and absenteeism. The current study extends the previous literature by examining the association between exposure to ACEs and truancy using self-reports from a representative sample of Florida high-school students. The findings reveal that exposure to ACEs is associated with truancy in a dose-response fashion. In addition, the findings provide some evidence that the association between ACEs and truancy is partially attenuated by school- and parenting-related variables.